Incorporating the range-based method into GridSim for modeling task and resource heterogeneity - Eng, Kailun (Institute of Electrical and Electronics Engineers, 2017)
Over the years, many heuristic algorithms have been proposed for solving various Grid scheduling problems. GridSim simulator has become a very popular simulation tool and has been widely used by Grid researchers to test and evaluate the performance of their proposed scheduling algorithms. As heterogeneity is one of the unique characteristics of Grid computing, which induces additional challenges in designing heuristic-based scheduling algorithms, the main concern when performing simulation experiments for evaluating the performance of scheduling algorithms is how to model and simulate different Grid scheduling scenarios or cases that capture the inherent nature of heterogeneity of Grid computing environment. However, most simulation studies that based on GridSim have not considered the nature of heterogeneity. In this paper, we propose a new simulation model that incorporates the range-based method into GridSim for modeling and simulating heterogeneous tasks and resources in order to capture the inherent heterogeneity of Grid environments that later can be used by other researchers to test their algorithms.